The Use of a Risk-Based Approach in Safety Issues of Coal Mines - KORSHUNOV, Gennady I.; RUDAKOV, Marat L.; KABANOV, Eugeniy I. (Journal of Environmental Management and Tourism; Vol 9 No 1 (2018): JEMT Volume IX Issue 1(25) Spring 2018DO - 10.14505//jemt.v9.1(25).23, 2018)
The paper contains the analysis of the data on major industrial accidents and occupational injuries at the coal mine industry enterprises of Russia in order to reveal statistically significant correlations between the indicators impacting the accident rate and the employees’ death risk level. As the risk criteria, the values of the methane-air resultant mixtures (MARM) explosions frequency and the frequency of the staff exposure at MARM explosions in the mines (observed levels of personal risks) are taken. The Kolmogorov–Smirnov test and Kruskal–Wallis test are used to analyze the categorized data samplings over the period from 2005 to 2016. The authors have defined the influence of relative gas content and hazard of layers regarding spontaneous combustion on the MARM explosions frequency. The regression models that take into consideration the impact of hazardous factors on the risk indicators have been received. The results of the performed coal mines ranging in Russia have been presented according to the level of individual risk, caused by MARM explosions; the received results have been compared with the acceptable tolerable risk level. The relevance of applying the research findings has been shown at the implementation of the dynamic model of the risk-based approach for ensuring coal mines safe exploitation.